Essay Writing / For Academic Purposes - Sivridou Fotini (Interbooks, 1999)
Introduction, Sentence Writing, Paragraph Writing, Points to Remember, The Essay, Note Taking, Summaries, Reports, Appendix/ The Research Paper, Glossary, Bibliography.
Introduction, Sentence Writing, Paragraph Writing, Points to Remember, The Essay, Note Taking, Summaries, Reports, Appendix/ The Research Paper, Glossary, Bibliography.